2020
DOI: 10.1190/geo2019-0016.1
|View full text |Cite
|
Sign up to set email alerts
|

Low-rank matrix decomposition method for potential field data separation

Abstract: Separation of potential field data forms the basis of inversion and interpretation. The low-rank matrix theory is used for the separation of potential field data. A theoretical analysis led to the approximate equation that demonstrates the relation between the amplitudes of the wavenumber components of potential field data and the singular values of the trajectory matrix embedded from the potential field data matrix. Therefore, the low-rank feature of the trajectory matrix of regional field data and the sparse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The impact of the choice of the parameters on the computational cost and the quality of the solutions is investigated. [32]. Experiments demonstrated that the results are consistent for a large subinterval.…”
Section: 2mentioning
confidence: 67%
See 2 more Smart Citations
“…The impact of the choice of the parameters on the computational cost and the quality of the solutions is investigated. [32]. Experiments demonstrated that the results are consistent for a large subinterval.…”
Section: 2mentioning
confidence: 67%
“…r j e iφj e iuj m+ivj n , where (u j , v j ), r j , and φ j denote the 2D wavenumber, amplitude, and phase of the jth 2D component, respectively. It is also proved in [32] that rank(T) = J, and…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Zhu et al. (2020) derived a relation between the rank of ℋ( T ) and J , which is expressed as follows: rank(scriptH(T))=J. $\text{rank}(\mathcal{H}(\boldsymbol{T}))=J.$ …”
Section: Methodsmentioning
confidence: 99%
“…Here, we use ℋ to denote the block Hankelization operator. Zhu et al (2020) derived a relation between the rank of ℋ(T) and J, which is expressed as follows:…”
Section: Why Can the Target Magnetic Anomaly Be Extracted From The To...mentioning
confidence: 99%